2019
DOI: 10.18546/lre.17.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Educating teachers towards global citizenship: A comparative study in four European countries

Abstract: This article, derived from a larger EU-funded empirical research project, draws on a comparative analysis of pioneering global citizenship education (GCE) in-service primary teacher education programmes, as theorized and practised in four European countries, to explore how higher education institutions (HEIs), non-governmental organizations (NGOs) and participating teachers shape the development of content-based, competence-based and values-based approaches to teacher education. With reference to the multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
(42 reference statements)
0
14
0
6
Order By: Relevance
“…The data show that there is little association between CGCE and levels of critical literacy. As Kim (2019) and Tarozzi and Mallon (2019) have pointed out, this may be due to the few opportunities for CGCE to be part of teacher training, nor were there any references to postcolonial discourses, which may be due to the excessive presence of the Eurocentric perspective in the training programmes for teachers of history and social sciences. The postcolonial discourse tends to be core in theoretical approaches to CGCE (Andreotti 2006) in reaction to Eurocentric discourses or those centred on economic factors, which tend to be hegemonic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data show that there is little association between CGCE and levels of critical literacy. As Kim (2019) and Tarozzi and Mallon (2019) have pointed out, this may be due to the few opportunities for CGCE to be part of teacher training, nor were there any references to postcolonial discourses, which may be due to the excessive presence of the Eurocentric perspective in the training programmes for teachers of history and social sciences. The postcolonial discourse tends to be core in theoretical approaches to CGCE (Andreotti 2006) in reaction to Eurocentric discourses or those centred on economic factors, which tend to be hegemonic.…”
Section: Discussionmentioning
confidence: 99%
“…Teacher training programmes must include spaces that allow for debate on news items with a global perspective (Kim 2019;Tarozzi and Mallon 2019;Sant 2018) in order for CGCE to have a greater presence in teacher training. By doing so, teachers will better understand the global dimensions of news items (O'Meara et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In direct response to the above calls to mainstream GCE as a possibility to educate citizens to build a more sustainable world, governments around the world have been including GCE in their education policy documents and curricula, yet with different emphasis between countries as a result of diverse socio-economic, political and historical contexts. For instance, across Europe, GCE has become increasingly popular framed by the growing displacement of people fleeing violence and environmental disaster across European borders, a rise in rightwing populism across the continent and the threat of terror and radicalization (Tarozzi and Mallon, 2019). Nonetheless, the latest reports on progress toward meeting target 4.7 have concluded that worldwide GCE levels remain low.…”
Section: Educating Global Citizens For a More Sustainable Worldmentioning
confidence: 99%
“…I call such learning 'global learning', using the definition of the Maastricht Declaration of the GENE/European Council from 2002: 'Education, that opens people's eyes and minds to the realities of the world, and awakens them to bring about a world of greater justice, equity and human rights for all ' (Maastricht Global Education Declaration, 2002;Nygard and Wegimont, 2018; see also other scholars such as Bourn, 2014Bourn, , 2018Lehtomäki, 2019;Lehtomäki et al, 2016;2017;Räsänen, 2009;Tarozzi and Mallon, 2019). This concept is seen as an umbrella concept of 'global citizenship education' (cf.…”
Section: Global Developments and The Concepts Of World Societymentioning
confidence: 99%